Crossfire [large type] - Eason, Lynette (Eason, Lynette. Extreme measures, 2022)
"FBI special agent Julianna Jameson is a top-notch negotiator who has never lost a hostage. Surely she can manage to take care of her much younger sister, Dottie, who showed up unannounced to live with Julianna while she finished her senior year of high school.A former sniper with the 75th Ranger Regiment, Clay Fox left the army after a tragic incident that he can't get past. Now he's working as a high school resource officer until he can figure out what to do with the rest of his life. Their paths cross when Julianna is called in to negotiate a courtroom hostage situation involving Clay's sister. Impressed and a bit intimidated by the calm, capable woman with the dark hair and blue eyes, Clay invites her to speak at his school. Dottie's school.But as the anniversary of a school shooting from Julianna's past approaches, it becomes clear that her perfect record is about to be tested and that Dottie is at risk. If Julianna and Clay can't figure out who's behind the attacks, more innocent people will die--and Dottie is next in line.This intense story of revenge and redemption from bestselling author and master of suspense Lynette Eason will have you up all night as you race toward the explosive finish"--